2002
DOI: 10.1128/iai.70.12.7013-7021.2002
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Variant Rifin Antigens by Human Antibodies Induced during Natural Plasmodium falciparum Infections

Abstract: Antibodies from individuals living in areas where malaria is endemic are known to react with parasitederived erythrocyte surface proteins. The major immunogenic and clonally variant surface antigen described to date is Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP-1), which is encoded by members of the multicopy var gene family. We report here that rifin proteins (RIF proteins), belonging to the largest known family of variable infected erythrocyte surface-expressed proteins, are also naturally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 34 publications
0
65
0
Order By: Relevance
“…Variant antigen families in Plasmodium species have been shown to be immunogenic (1,2,14,16), and antibodies produced against them are variant specific and thought to play a role in protection (31,36). One example of a known variant antigen family in P. berghei is bir, a homologue of the major variant antigen family in malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Variant antigen families in Plasmodium species have been shown to be immunogenic (1,2,14,16), and antibodies produced against them are variant specific and thought to play a role in protection (31,36). One example of a known variant antigen family in P. berghei is bir, a homologue of the major variant antigen family in malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Such associations have been reported in the context of responses to VSA expressed by both autologous and heterologous parasite isolates, which may contribute to the putatively rapid acquisition of immunity to malaria (24). P. falciparum erythrocyte membrane protein-1 (PfEMP-1) is considered to be the principal target of anti-VSA antibodies, although rifin proteins, a second, polymorphic, parasite-derived family of antigens that are inserted into the infected erythrocyte membrane, also induce antibody responses in exposed populations (2,7,31,32,42). Studies incorporating longitudinal components have shown that, in most but not all cases, antibodies with specificity for the VSA expressed by the autologous parasites causing a given malaria attack are infrequent or absent prior to the attack but are enhanced and sustained posttreatment (10,13,21,26,37,46).…”
mentioning
confidence: 99%
“…The recombinant rifins used in this study were purified on affinity columns to 95% homogeneity, and plasma immunoglobulin G antibody responses to the purified His 6 -Rif proteins were measured by a standard enzyme-linked immunosorbent assay by using previously established procedures and conditions (1). Blank values were determined in parallel with each individual test serum with no antigen in the well.…”
Section: Methodsmentioning
confidence: 99%
“…A large cross-sectional survey of individuals exposed to natural P. falciparum infections was carried out recently to evaluate the presence in their sera of specific antirifin antibodies capable of recognizing recombinant rifin proteins. The most significant finding was the high frequency of recognition by malaria-exposed immune adults whereas semi-immune children were less reactive (1). In this study, serum samples available from a longitudinal study were analyzed for specific antirifin antibodies to find whether rifin antibodies play a role in natural immunity to malaria.…”
mentioning
confidence: 99%